Estuarine Ichthyoplankton Studies – A Review - Zhang, Hui; Wang, Yibang; Liang, Cui; Liu, Shude; Xian, Weiwei (Frontiers in Marine Science, 2022)
Estuaries are nutrient-rich environments with a gradient of fresh to salt water. They support high primary productivity and an abundance of zooplankton. Estuaries are used by many fish as nursery grounds because their environmental conditions provide abundant food for larval and adult fish. Ichthyoplankton, which comprise fish eggs and larvae, are important for the recruitment of fish species. At present, there are no systematic reviews on ichthyoplankton in estuaries from a global perspective. Here, research on ichthyoplankton over the last 60 years (1951–2022) was reviewed, focusing on three aspects: evaluation of ichthyoplankton published studies, community structure, and factors affecting community structure. The results show that research on estuarine ichthyoplankton has increased, from less than 1 article per year in the 1950s to more than 30 articles per year in the 2020s. The keyword used most commonly was ‘community structure’ and ‘dynamics’ and the word used most recently was ‘climate change’. Regarding the geographical distribution of the studies carried out on estuarine ichthyoplankton, USA had the most (32.9% of all studies), followed by Australia (8.1%), South Africa (6.1%), Brazil (5.6%), Japan (5.1%), China (4.9%), Canada (4.8%), and Portugal (4.8%). Salinity and turbidity were the main factors affecting the ichthyoplankton community structure in estuaries. Climate change indirectly affected the community structure of estuarine ichthyoplankton by changing the spawning time, spawning location, and hatching time of species. The movement of spawning sites poleward and the advance of spawning time showed a consistent trend. In addition, the development of DNA barcoding techniques will be a useful supplement to traditional taxonomic methods for identifying ichthyoplankton and will provide new opportunities for the development of systematic taxonomy in this field. Our review contributes to a broader understanding of estuarine ichthyoplankton and provides theoretical support for estuarine environmental protection and the sustainable use of estuarine fishery resources.